MESIN PENGOLAH LIMBAH SAMPAH PLASTIK MENJADI BAHAN BAKAR ALTERNATIF - Prasetyo, Hendra; Rudhiyanto, Rudhiyanto; Fitriyanto, Ilham Eka (Program Kreativitas Mahasiswa - Teknologi, 2014)
Plastic waste is a global-scale environmental issues since it is very difficult to disen tangle. According to UNNES data research team in 2010, the amount of garbage volume in the area and its surrounding is 20 m3 / day, and 3% of it is plastic which is very difficult to be unraveled. The solution toward the case so far is by burning; meanwhile, it can result pollutants that can damage the environment, such as NOx, SOx, CO, and others. Hence, the need for solution that is more promising and prospecting by recycling plastic into alternative fuel. The method we use in this program is identifying the problem and its solution. Identification of problems which we conclude is designing a plastic treatment plant to be alternative fuel. Then, we do manufacture and assemble equipment. After that, we perform testing and analysis and draw conclusions. This machine is made with a production capacity of 0.5 liters / 30 minutes, with a length of 1 m, width 0.35 m, height 1.35 m. The advantage of the existence of this machine is environmentally friendly, safe, and having large capacity so that it can reduce the waste of plastic that causes pollution in the environment and the surrounding of Banaran TPS.Keywords: Processing, plastic waste, alternative fuel